2019
DOI: 10.1155/2019/4138534
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Amounts of Cinnamon Consumption on Blood Glucose in Healthy Adult Individuals

Abstract: Background. This study was aimed at investigating the effect of consumption of different amounts of cinnamon on preprandial blood glucose (PrBG), postprandial blood glucose (PoBG), glycosylated hemoglobin (HbA1c), and body mass index (BMI). Methods. This study was carried out on 41 healthy adult individuals. The individuals were divided into 3 groups and monitored for 40 days. The first, second, and third groups were given 1 g/day, 3 g/day, and 6 g/day cinnamon, respectively. Before the beginning of the consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
1
3
0
3
Order By: Relevance
“…This trend was also observed in these type of extracts when exposed to Type 2 diabetes patients after menopause (Vanschoonbeek et al, 2006). Our results are in accordance with previous study which demonstrated the potential of C. cassia extracts enhance the activity of glycogen synthase, thus, increasing glycogen storage rather than glucose uptake (Kizilaslana and Erden, 2019). Parallel findings reported by Cao et al (2007) have also showed the reduced levels of insulin receptor-β than the absorption of glucose in the mouse 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 92%
“…This trend was also observed in these type of extracts when exposed to Type 2 diabetes patients after menopause (Vanschoonbeek et al, 2006). Our results are in accordance with previous study which demonstrated the potential of C. cassia extracts enhance the activity of glycogen synthase, thus, increasing glycogen storage rather than glucose uptake (Kizilaslana and Erden, 2019). Parallel findings reported by Cao et al (2007) have also showed the reduced levels of insulin receptor-β than the absorption of glucose in the mouse 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 92%
“…e bioactive compounds in tea have the ability to influence signal pathways and key molecules involved in the regulation of insulin, blood sugar, and energy metabolism [79]. On the other hand, the biologically active substances in cinnamon mimic insulin-like properties, including activating insulin kinase, increasing glucose uptake, and autophosphorylating the insulin receptor [80]. A study conducted by Hong et al [81] found that the cinnamon peel extract increases insulin sensitivity and raises glucose intake.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, cinnamon's effectiveness in lowering plasma glucose appears most pronounced in individuals with poorly controlled diabetes (Medagama and Bandara, 2014). Studies have indicated that an effective dose consists of 112 mg of aqueous extract taken three times daily, equivalent to a daily intake of 3 grams of Cinnamomum cassia (Kizilaslan and Erdem, 2019). Furthermore, research, including the work of Allen and colleagues, underscores the benefits of cassia cinnamon in reducing fasting plasma glucose levels compared to a placebo.…”
Section: Cinnamon (Cinnamomum Cassia)mentioning
confidence: 99%